Pragmatic Analysis of Figurative Language in The Moon and Her Secrets - Rachmaningtyas, Amelia Jacklyn; Sabat, Yulianto; Aisyah, Siti; Prasetyo, Yudy (Journal of English Language and Education, 2025)
This study identifies and analyzes the types of figurative language in Leony Jardine's poetry collection The Moon and Her Secrets, interpreting their contextual meanings through a pragmatic perspective. Employing a qualitative descriptive method and Keraf’s classification, the research reveals that metaphor is the most frequently used device, followed by simile, with limited occurrences of personification, allusion, eponym, epithet, hypallage, irony, satire, and innuendo. These figurative expressions serve not only as stylistic devices but also convey emotional, symbolic, and interpersonal meanings shaped by context and speaker intention. Through close reading and contextual analysis, this study demonstrates how figurative language acts as a pragmatic strategy in poetic communication, enhancing the reader’s emotional engagement and understanding of the text. The findings indicate that poetic language fulfills both aesthetic and communicative purposes in expressing complex human experiences.